Analgesic tolerance and cross-tolerance to the bifunctional opioid/neuropeptide FF receptors agonist EN-9 and μ-opioid receptor ligands at the supraspinal level in mice. (February 2023) - Han, Zhenglan; Jin, Guofei; Tang, Jiancai; Wang, Hanyan; Guo, Dongmei; Zhang, Jingping
Abstract: The chimeric peptide EN-9 was reported as a κ-opioid/neuropeptide FF receptors bifunctional agonist that modulated chronic pain with no tolerance. Many lines of evidence have shown that the effect of the κ-opioid receptor is mediated by not only its specific activation but also downstream events participation, especially interaction with the μ-opioid receptor pathway in antinociception and tolerance on most occasions. The present study investigated the acute and chronic cross-tolerance of EN-9 with μ-opioid receptor agonist EM-2, DAMGO, and morphine after intracerebroventricularly (i.c.v) injection in the mouse tail-flick test. In the acute tolerance test, EN-9 showed symmetrical acute cross-tolerance to DAMGO but no cross-tolerance to EM2. In the chronic tolerance test, EN-9 had no tolerance after eight days of repeated administration. However, EN-9 illustrated complete cross-tolerance to morphine and symmetrical cross-tolerance to EM2. In addition, inhibition of NPFF receptor could induce the tolerance development of EN-9. These findings indicated that supraspinal EN-9-induced antinociception contains additional components, which are mediated by the downstream μ-opioid receptor pathway both in acute and chronic treatment, whereas the subtypes of μ-opioid receptor or NPFF system pathway involved in antinociceptive effects induced by EN-9 are complex. Identifying the receptor mechanism could help design preferable bifunctional opioid compounds. Highlights: EN-9 is a new chimeric peptide exerted significant analgesic effect with non-tolerance. EN-9 activates different pathways in acute and chronic treatment. Identify the underlying mechanism of EN-9 could help design preferable bi-functional or/and multi-functional opioid compounds